Leveraging IT Assets Integrating XML and relational data. - Singh, Anupam
XML is establishing itself as the standard for exchange of information across enterprises. However, the technology that allows enterprise-class applications to deal with XML processing is still not clearly formulated. This causes most enterprise customers to implement their own architecture. Additionally, their software implementations try to deal with the same set of basic XML processing questions in different layers of the enterprise, rather than as a whole.